United States Dilemma of Strategic Alliance with Pakistan: From ‘Policy of Containment’ to ‘War against Terrorism’ - Dr. Adam Saud; Dr. Tauqeer Hussain Sargana; Dr. Mujahid Hussain (Journal of Political Studies, 2019)
This study has questioned the very legitimacy and ability of United States to honor bilateral relations that it commits under strategic partnerships. The investigation makes the point that partner nations with United States are used as a tool to pursue foreign policy priorities in regions of strategic interest. Partner nations are usually vulnerable to United States international influence in political, economic, diplomatic and military domains. United States due to its international leverage most of the time gets an easy way out in the so-called strategic partnerships but at times when partner nations are in need of dire support, Washington prefers to backtrack from its commitments. This paper has considered South Asia as a case study to contest United States context of „strategic alliance‟ as a mean to pursue foreign policy priorities with Pakistan. The vulnerabilities of Pakistan time and again have allowed United States to positively negotiate best deals for Washington, which in-turn brought political complications for the partner nation. This study makes the point that nature of bilateral relations between Pakistan and United States are multifaceted, whereas the phenomenon of „containment of communism‟ initially the Soviet and now the Chinese had become the most decisive factor behind their strategic orientation. US failure to attain its objectives from Pakistan had always made India the ultimate choice, which in turn uses Washington‟s leverage to craft South Asian political order in its favor. The study has applied inductive method with that of „Analytical Eclecticism‟ approach to evaluate the ups and downs of the two inconvenient strategic allies and decoded the so-called premises of the Indo-US strategic alliance which is founded on the political orchestration to contain Chinese increasing influence.